2005
DOI: 10.1007/s00425-005-0142-7
|View full text |Cite
|
Sign up to set email alerts
|

Sucrose synthase and RuBisCo expression is similarly regulated by the nitrogen source in the nitrogen-fixing cyanobacterium Anabaena sp.

Abstract: In higher plants and cyanobacteria, sucrose (Suc) metabolism is carried out by a similar set of enzymes. The function and regulation of Suc metabolism in cyanobacteria has begun to be elucidated. In strains of Anabaena sp., filamentous nitrogen-fixing cyanobacteria, Suc synthase (SuS, EC 2.4.1.13) controls Suc cell level through the cleavage of the disaccharide. The present work shows that there are two sus genes in Anabaena (Nostoc) sp. that are co-regulated regarding the nitrogen source; however, only susA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
49
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(66 citation statements)
references
References 35 publications
(52 reference statements)
7
49
0
Order By: Relevance
“…was recently demonstrated by Curatti et al (2002), who showed that diazotrophic growth was impaired in a mutant strain overexpressing SuS. Curatti et al (2006) later showed that expression of SuS and Rubisco, a key enzyme in CO 2 fixation during photosynthesis, is similarly downregulated by a N source-dependent developmental program in the heterocysts.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…was recently demonstrated by Curatti et al (2002), who showed that diazotrophic growth was impaired in a mutant strain overexpressing SuS. Curatti et al (2006) later showed that expression of SuS and Rubisco, a key enzyme in CO 2 fixation during photosynthesis, is similarly downregulated by a N source-dependent developmental program in the heterocysts.…”
mentioning
confidence: 88%
“…Suc can either be cleaved by SuS or irreversibly hydrolyzed by two alkaline/neutral invertases (A/N-Inv) when there is high demand for hexoses (Porchia and Salerno, 1996;Cumino et al, 2001Cumino et al, , 2002Curatti et al, 2002;Vargas et al, 2003). Curatti et al (2002Curatti et al ( , 2006 showed SuS to be involved in the cleavage of Suc only in vegetative cells in vivo. Besides, in contrast to a previous report, it has recently been shown that A/N-Invs are also expressed in vegetative cells (Schilling and Ehrnsperger, 1985;Curatti et al, 2002;Vargas et al, 2003).…”
mentioning
confidence: 99%
“…It was first thought that sucrose metabolism was a characteristic of plants, but it was later found in other oxygenic photosynthetic organisms (4,5). In the last decade, Salerno and coworkers demonstrated the importance of sucrose for carbon and nitrogen fixation in filamentous cyanobacteria (6,7). More recently, genomic and phylogenetic analyses revealed the existence of sucrose-related genes in nonphotosynthetic prokaryotes such as proteobacteria, firmicutes, and planctomycetes (4,5,8).…”
mentioning
confidence: 99%
“…Cyanobacteria exposed to long-term nitrate starvation demonstrate extreme loss of photosynthetic activity and strong bleaching, but the cells remain viable (Sauer et al, 2001). When nitrogen availability changes, cyanobacteria can rebalance the uptake and assimilation of nitrogen (Herrero et al, 2001;Espinosa et al, 2006) and adapt their overall metabolism, including that for carbon fixation and sugar metabolism (Miller et al, 2002;Curatti et al, 2006;Osanai et al, 2006Osanai et al, , 2007.…”
mentioning
confidence: 99%